The Crisis Of Low Oil Prices And Its Impact On Energy Consumption Globally During The Corona Pandemic - An Analytical Study Of Oil Market Indicators In 2019 And 2020 (مجلة الواحات للبحوث والدراسات, 2023)
Abstract: The present study aims to analyze the impact of the coronavirus pandemic on oil prices and energy consumption in the world by studying and analyzing global oil and gas market indicators from the last quarter of 2019 to the end of 2020. In pursuance of this aim, the researchers relied on the descriptive and analytical approach of using global data and statistics, through which it was concluded that the impact of the pandemic on oil prices appears through the low levels of global demand and consumption of oil and gas due to the lockdown policy and the precautionary measures taken in an attempt to prevent the spread of the virus.Keywords : Corona pandemic, oil prices, energy consumption, global markets, economic growth.